Global Perspectives on International Student Experiences in Higher Education : Tensions and Issues - Tozini, Kelber (Journal of International Students, 2020)
In Global Perspectives on International Student Experiences in Higher Education, Dr. Krishna Bista selected 18 studies that present important findings to the field, in which the authors provide examples of how the quality of the international student experience deserves the utmost attention of administrators, faculty, student affairs professionals, and policymakers. The book is divided into four main units, which are described separately in this review.